2021
DOI: 10.1007/s13205-020-02610-w
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potent drug inhibitors against SARS-CoV-2 RNA polymerase: an in silico approach

Abstract: has emerged as a rapidly escalating serious global health issue, affecting every section of population in a detrimental way. Present situation invigorated researchers to look for potent targets, development as well as repurposing of conventional therapeutic drugs. NSP12, a RNA polymerase, is key player in viral RNA replication and, hence, viral multiplication. In our study, we have screened a battery of FDA-approved drugs against SARS-CoV-2 RNA polymerase using in silico molecular docking approach. Identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“… 7BV2 AutoDock Vina, Glide, rDock GROMACS 1615 FDA-approved drugs, ZINC database Leucal, Natamycin, Folic Acid [101] 7BW4 DockThor, Autodock Vina, PatchDock GROMACS 48 antivirals Ribavirin, Zanamivir, Penciclovir [141] 6M71 AutoDock Vina GROMACS 92 phytochemicals Hesperidin, Rutin, Quercetin [69] 7BTF AutoDock Vina NAMD VMD Novel adenosine derivatives 4 unamed adenosine derivates [142] 6M71 Autodock 4.0.1. - 65 FDA approved small molecule Raltegravir, Indinavir, Tipranavir, Dolutegravir, Etravirine [143] 6M71 Moe-Dock GROMACS 63 anti-viral drugs approved by the FDA Ledipasvir, Remdesivir, Paritaprevir [144] 6M71 AutoDock Vina - Flavonoids, phenolic acids, and terpenes p-Coumaric Acid, Ellagic Acid, Kaempferol, Quercetin [145] 6M71 Discovery studio Desmond Zinc15 DataBank Paritaprevir, Glecaprevir, Velpatasvir, Remdesivir, Ribavirin [146] …”
Section: Targeted Proteins Using In Silico Methodsmentioning
confidence: 99%
“… 7BV2 AutoDock Vina, Glide, rDock GROMACS 1615 FDA-approved drugs, ZINC database Leucal, Natamycin, Folic Acid [101] 7BW4 DockThor, Autodock Vina, PatchDock GROMACS 48 antivirals Ribavirin, Zanamivir, Penciclovir [141] 6M71 AutoDock Vina GROMACS 92 phytochemicals Hesperidin, Rutin, Quercetin [69] 7BTF AutoDock Vina NAMD VMD Novel adenosine derivatives 4 unamed adenosine derivates [142] 6M71 Autodock 4.0.1. - 65 FDA approved small molecule Raltegravir, Indinavir, Tipranavir, Dolutegravir, Etravirine [143] 6M71 Moe-Dock GROMACS 63 anti-viral drugs approved by the FDA Ledipasvir, Remdesivir, Paritaprevir [144] 6M71 AutoDock Vina - Flavonoids, phenolic acids, and terpenes p-Coumaric Acid, Ellagic Acid, Kaempferol, Quercetin [145] 6M71 Discovery studio Desmond Zinc15 DataBank Paritaprevir, Glecaprevir, Velpatasvir, Remdesivir, Ribavirin [146] …”
Section: Targeted Proteins Using In Silico Methodsmentioning
confidence: 99%
“…Furthermore, the antiviral mechanisms of these drugs (remdesivir, lopinavir/ritonavir, and chloroquine/hydroxychloroquine) against SARS-CoV-2 have been thoroughly reviewed by Uzunova et al (2020) [160]. performed docking-based virtual screening from a library of 1764 antiviral drugs against SARS-CoV-2 NSP12 (RNA polymerase) and identified five compounds, viz., paritaprevir, glecaprevir, velpatasvir, remdesivir, and ribavirin which exhibited high-binding affinity with the drug target [161]. Gowrishankar et al (2021) screened a total of 57 phytochemicals from three most commonly used Indian herbs (Justicia adhatoda, Eucalyptus globulus, and Vitex negundo) used in "steam inhalation therapy" against four structural protein targets of SARS-CoV-2 viz.…”
Section: Case Study Of Covid-19mentioning
confidence: 99%
“…In silico drug design and discovery of RdRp inhibitors are given in Table 7. In addition to remdesivir and ribavirin, the molecular docking study of 1,749 antiviral drugs suggested that paritaprevir, glecaprevir, and velpatasvir also showed interesting interactions with RdRp (Singh et al, 2021). The top 50 compounds retrieved from structure-based virtual screening of 15,220 compounds from DrugBank and TargetMol Bioactive compounds Library against SARS-CoV-2 RdRp were evaluated by bio-layer interferometry (BLI) binding followed by cell-based polymerase activity assays .…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%